THE IMPACT OF USING EDUCATIONAL MEDIA ON STUDENTS OF ENGLISH AS A FOREIGN LANGUAGE'S READING COMPREHENSION - Syafrizal Syafrizal (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
The purpose of this research is to see if educational media can help English as a foreign language (EFL) students improve their reading skills. This proposal for a research paper will poll Indonesian students who are currently studying English. The purpose of this paper proposal is to demonstrate the influence of EFL students using educational learning media as well as the students' experiences with educational media as a learning aid. This study's demographic consists of Indonesian volunteers (students) who are currently studying English. A total of 20 participants have been discovered by the researcher. The population was most likely sampled using a simple random sampling procedure. The researcher used questionnaires to gain information about the students' attitudes toward media use as a data collection approach. As a result, instructional media is beneficial in improving and increasing pupils' reading comprehension skills.